THREE DECADES OF HEART TRANSPLANTATION IN THE SHUMAKOV CENTER: LONG-TERM OUTCOMES - S. V. Gautier; A. O. Shevchenko; A. Ya. Kormer; V. N. Poptsov; R. Sh. Saitgareev; D. V. Shumakov; V. M. Zakharevich (Вестник трансплантологии и искусственных органов)
.